Consumption in Germany during the Period of Rearmament - Nathan, Otto (Quarterly Journal of Economics, 1942)
Consumption under the impact of rearmament, 349. — The problem of estimating the effect of rearmament upon consumption, 351. — Methods of analysis, 352. — The national income and the share of all wage and salary earners, 355. — The income of employed wage and salary earners subject to social insurance, 358. — Wages and income of individual wage earners, 366. — The production of consumers' goods, 369. — The consumption of consumers' goods, 372. — Per capita consumption of individual commodities, 374. — Consumption of individual commodities in the budgets of typical families, 376. — Deterioration in the quality of consumers' goods, 378. — Changes in the satisfaction of collective needs, 379. — Conclusions, 382.